Values of Donor Serum Lipids and Calcium in Predicting Graft Function after Kidney Transplantation: A Retrospective Study - Shi, Hui-bo; Zhao, Yuan-yuan; Li, Yu; Li, Yi; Liu, Bin; Gong, Nian-qiao; Chang, Sheng; Du, Dun-feng; Zhu, Lan; Xu, Jing; Li, Xiao-qin; Zeng, Meng-jun; et al. (Current medical science, 2023)
Objective Delayed graft function (DGF) and early graft loss of renal grafts are determined by the quality of the kidneys from the deceased donor. As “non-traditional” risk factors, serum biomarkers of donors, such as lipids and electrolytes, have drawn increasing attention due to their effects on the postoperative outcomes of renal grafts. This study aimed to examine the value of these serum biomarkers for prediction of renal graft function. Methods The present study consecutively collected 306 patients who underwent their first single kidney transplantation (KT) from adult deceased donors in our center from January 1, 2018 to December 31, 2019. The correlation between postoperative outcomes [DGF and abnormal serum creatinine (SCr) after 6 and 12 months] and risk factors of donors, including gender, age, body mass index (BMI), past histories, serum lipid biomarkers [cholesterol, triglyceride, high-density lipoprotein (HDL) and low-density lipoprotein (DL)], and serum electrolytes (calcium and sodium) were analyzed and evaluated. Results (1) Donor age and pre-existing hypertension were significantly correlated with the incidence rate of DGF and high SCr level (≥2 mg/dL) at 6 and 12 months after KT ( P <0.05); (2) The donor’s BMI was significantly correlated with the incidence rate of DGF after KT ( P <0.05); (3) For serum lipids, merely the low level of serum HDL of the donor was correlated with the reduced incidence rate of high SCr level at 12 months after KT [ P <0.05, OR (95% CI): 0.425 (0.202–0.97)]; (4) The serum calcium of the donor was associated with the reduced incidence rate of high SCr level at 6 and 12 months after KT [ P <0.05, OR (95% CI): 0.184 (0.045–0.747) and P <0.05, OR (95% CI): 0.114 (0.014–0.948), respectively]. Conclusion The serum HDL and calcium of the donor may serve as predictive factors for the postoperative outcomes of renal grafts after KT, in addition to the donor’s age, BMI and pre-existing hypertension.